1982
DOI: 10.1002/ajp.1350030125
|View full text |Cite
|
Sign up to set email alerts
|

Development comparisons of grimace and play mouth in infant pigtail macaques (Macaca nemestrina)

Abstract: Five laboratory-born infant pigtail macaques (Macaca nemestrina) were studied during playroom interactions. Each infant was videotaped for a 5-minUte period weekly for 5 months. The animals were scored on the frequency of the mouth display observed. Both play-type (round mouth corners, ie, relaxed open-mouth display) and fear-type (sharp mouth corners, ie, silent bared-teeth display) facial expressions were present at the onset of observations. Play mouths appeared with greater frequency than fear mouths throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Three hypotheses, consistent with ones developed in the existing literature, were tested in this study. The first hypothesis is based on the concept of developmental immaturity, in that social signals may occur in a misdirected manner because young animals have not, as yet, narrowed their use to appropriate contexts (e.g., Kirkevold et al, 1982). The second hypothesis is based on the proposed function of play as a means for training for the unexpected (Špinka et al, 2001), whereby movements, including HS (Petrù et al, 2008), are interjected into playful sequences to provide the animals with the experience of loss of control and unpredictable outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three hypotheses, consistent with ones developed in the existing literature, were tested in this study. The first hypothesis is based on the concept of developmental immaturity, in that social signals may occur in a misdirected manner because young animals have not, as yet, narrowed their use to appropriate contexts (e.g., Kirkevold et al, 1982). The second hypothesis is based on the proposed function of play as a means for training for the unexpected (Špinka et al, 2001), whereby movements, including HS (Petrù et al, 2008), are interjected into playful sequences to provide the animals with the experience of loss of control and unpredictable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of infant pig-tailed macaques, it was reported that the first uses of the open mouth play face were indiscriminant, being used before mouthing either other monkeys or inanimate objects. Only later in development did the infants preferentially direct open mouths toward other monkeys (Kirkevold, Lockard, & Heestan, 1982). Similar findings are reported for polecats (Poole, 1978).…”
mentioning
confidence: 99%
“…This problem is even greater with infants, where opening the mouth may be directed to inappropriate targets, such as inanimate objects. While such inappropriate uses of the open mouth often have been interpreted as misdirected play signaling (e.g., Kirkevold, Lockard & Heestan, 1982), this interpretation is compromised not only by the infant monkey's penchant for indiscriminately mouthing its surroundings (Chalmers, 1984) but also by the fact that infants tend to have an exaggerated anticipatory opening of the mouth, which can lead to them having prolonged periods of sustained mouth opening before any oral contact (Goldfield, 1995).…”
mentioning
confidence: 99%
“…Submissive signals can be expressions of fear, postures that expose vulnerable regions of the body, or behavior patterns belonging to the mating or infantile repertoire. Although it is generally believed that the ability to display submissive signals is relatively independent from experience (Chevalier-Skolnikoff 1974a; Kirkevold et al 1982;Mason 1985), the usage of submissive signals is probably learned during development, through direct experience and observation of interactions between other individuals (Mason 1985). In other words, individuals learn during development that expressions of fear or other behavior patterns are likely to reduce the aggressive disposition of an opponent and learn to display these signals in situations with risk of aggression.…”
Section: Submissive Signals: Bared-teeth Display and Presentationmentioning
confidence: 99%
“…The play face consists of a wide opening of the mouth, as if to attempt to bite, but without clenching the teeth. The play face is displayed almost exclusively by juvenile and subadult macaques, namely the class of individuals that most engage in play, and occasionally by adult males (Symons 1978;Kirkevold et al 1982;Preuschoft 1992). Play faces are usually displayed simultaneously by two play partners and may be associated with soft vocalizations (Symons 1978;Preuschoft 1992).…”
Section: Affiliationmentioning
confidence: 99%